The Correlation between the Senior Secondary School Students' Habits of Listening to English Songs and Their Listening Ability - Sitti Kurnia Aziz; Muhammad Asfah Rahman; Munir Munir (Journal of Excellence in English Language Education, 2022)
The goal of this study was to see If there is a substantial difference relationship between the habit of listening to English songs as well as their listening skills. This study used quantitative methods and correlational research was used as a research strategy. This study's population consisted of students from SMA Negeri 2 class X Pangkep in the 2021/2022 school year. The samples were collected with the help of a cluster random sampling technique consisting of 37 students. The instrument of this research is a Questionnaire of 20 numbers and a Listening test of 30 numbers. From the analysis of data and computations, it was found that there was no relationship between students who like to listen to music and their listening ability. The result of rxy is -128, and after consultation with rtable, rxy (-128) < rtable (0.334). This means that there is no correlation. The significant worth of this research was 0.000 where significant degree used was -0.128. The hypothesis which states that There isn't any connection between habit in listening and listening abilities is (Ho) accepted so that the alternative hypothesis is rejected. Finally, there are a strong unfavorable relationship between listening habits and listening ability.